Aberrant prefrontal functional connectivity during verbal fluency test is associated with reading comprehension deficits in autism spectrum disorder: An fNIRS study - Chan, Melody M. Y.; Chan, Ming-Chung; Yeung, Michael K.; Wang, Shu-Mei; Liu, Duo; Han, Yvonne M. Y. (Frontiers in Psychology, 2022)
Children with autism spectrum disorder (ASD) show marked difficulties in reading comprehension, a complex cognitive skill fundamental to successful daily functioning that is associated with core executive functions. However, the neurophysiological mechanisms underlying reading comprehension deficits in these children remain elusive. Twenty-one right-handed males with high-functioning ASD (mean age = 10.24 years) and 23 age-, IQ-, educational level-, sex- and handedness-matched typically developing (TD; mean age = 10.14 years) individuals underwent a reading comprehension test and the semantic verbal fluency test that tapped core executive functions underlying reading comprehension during concurrent prefrontal functional near-infrared spectroscopy measurement. Participants’ information processing efficiency was also assessed. High-functioning ASD children exhibited general reading comprehension (main effect of group: F1,40 = 7.58, p =.009), selective verbal fluency deficits (Group x category interaction: F1,42 = 4.90, p =.032) and slower processing speed (t42 = 2.36, p =.023). Regarding the hemodynamics of the prefrontal cortex (PFC), although ASD individuals showed comparable patterns of PFC brain activation to their healthy counterparts, lower PFC intrahemispheric (main effect of group: F1,42 = 11.36, p =.002) and interhemispheric (main effect of group: F1,42 = 7.79, p =.008) functional connectivity were evident during the semantic verbal fluency test. At the whole-group level, poorer reading comprehension performance was associated with poorer performance in the semantic verbal fluency test (r42 =.508, p <.001). Moreover, poorer semantic verbal fluency test performance was associated with slower information processing speed (r42 = -.312, p =.044), which is associated with reduced left medial PFC functional connectivity (r42 = -.319, p =.040). Abnormal intrahemispheric and interhemispheric prefrontal hypoconnectivity is associated with deficits in executive processes essential for reading comprehension in ASD. Our study has provided important implications for the neuropsychological and neurophysiological mechanisms underlying reading comprehension deficits in ASD.